2021
DOI: 10.1029/2020jc016919
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐Based Emulator of Distant Swell Trains and Local Seas Approaching a Pacific Atoll

Abstract: The general understanding of coastal inundation in the low-lying nations of the Pacific areas relates flooding to extreme water levels (i.e., astronomical tides, sea level variability) or tropical cyclones (Hoeke et al., 2013). Nevertheless, distant-source swells are less studied (Hoeke et al., 2013) and are one of the main causes of coastal flooding in the Pacific (Ford et al., 2018). After traveling thousands of kilometers (Snodgrass et al., 1966), swell dissipation results in wave set-up due to breaking wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…A comparison between the method of Cagigal et al. (2021) and our simplified method showed little, negligible difference in the results.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…A comparison between the method of Cagigal et al. (2021) and our simplified method showed little, negligible difference in the results.…”
Section: Resultsmentioning
confidence: 57%
“…To investigate how much wave energy a particular atoll experiences from the open ocean, we extracted the directional energy spectra from two to four points surrounding each of the atolls and merged the spectra into one single “superpoint” spectrum loosely following Cagigal et al. (2021). As a simplification from Cagigal et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Ranasinghe et al [45] and Anderson et al [46] observed shoreline rotation at embayed beaches, and Trombetta et al [47] observed an alongshore sediment drift reversal with large consequences for coastal zone management and infrastructures. These remote swells can also drive dramatic overtopping [6] even at storm-free areas, such as in the Gulf of Guinea [1,48], facing the South Atlantic storm track, and in the Pacific due to distant tropical cyclones [17,[49][50][51].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Anderson et al (2019Anderson et al ( , 2021 developed the Time-varying Emulator of Short and Long-term Analysis (TESLA) for coastal flood hazard assessment and applied the approach in San Diego, CA, by linking emulated TWLs with synoptic scale climate patterns at interannual (El Niño Southern Oscillation, ENSO) through intra-seasonal (Madden Julian Oscillation, MJO) timescales. Importantly, few statistical emulators (Anderson et al, 2019;Cagigal et al, 2020Cagigal et al, , 2021 incorporate atmospheric forcing, which can be crucial for understanding the drivers of extreme coastal flood events as suggested by Barnard et al (2015) and Marcos et al (2015).…”
Section: Mukhopadhyay Et Almentioning
confidence: 99%